Pharmacokinetics, SAfety/tolerability, and EFficacy of high-dose RIFampicin in tuberculosis-HIV co-infected patients on efavirenz- or dolutegravir-based antiretroviral therapy: study protocol for an open-label, phase II clinical trial (SAEFRIF) - Nabisere, Ruth (Trials, 2020)
BACKGROUND: Tuberculosis (TB) is a significant public health problem that causes substantial morbidity and mortality. Current first-line anti-TB chemotherapy, although very effective, has limitations including long-treatment duration with a possibility of non-adherence, drug interactions, and toxicities. Dose escalation of rifampicin, an important drug within the regimen, has been proposed as a potential route to higher treatment efficacy with shorter duration and some studies have suggested that dose escalation is safe; however, these have almost entirely been conducted among human immunodeficiency (HIV)-negative TB patients. TB-HIV co-infected patients on antiretroviral therapy (ART) are at increased risk of drug-drug interactions and drug-related toxicities. This study aims to determine the safety of higher doses of rifampicin and its effect on the pharmacokinetics of efavirenz (EFV) and dolutegravir (DTG) in TB-HIV co-infected patients. METHODS: This study is a randomized, open-label, phase IIb clinical trial among TB-HIV infected adult outpatients attending an HIV clinic in Kampala, Uganda. Patients newly diagnosed with TB will be randomized to either standard-dose or high-dose rifampicin (35 mg/kg) alongside standard TB treatment. ART-naïve patients will be randomly assigned to first-line ART regimens (DTG or EFV). Those who are already on ART (DTG or EFV) at enrollment will be continued on the same ART regimen but with dose adjustment of DTG to twice daily dosing. Participants will be followed every 2 weeks with assessment for toxicities at each visit and measurement of drug concentrations at week 6. At the end of intensive-phase therapy (8 weeks), all participants will be initiated on continuation-phase treatment using standard-dose rifampicin and isoniazid. DISCUSSION: This study should avail us with evidence about the effect of higher doses of rifampicin on the pharmacokinetics of EFV and DTG among TB-HIV co-infected patients. The trial should also help us to understand safety concerns of high-dose rifampicin among this vulnerable cohort. TRIAL REGISTRATION: ClinicalTrials.gov, ID: NCT03982277. Registered retrospectively on 11 June 2019.